Development of highly reinforced maleated natural rubber nanocomposites based on sol–gel‐derived nano alumina. Issue 18 (18th January 2018) - Roy, Kumarjyoti; Jatejarungwong, Chainut; Potiyaraj, Pranut
ABSTRACT: In the present study, sol–gel synthesized alumina (Al2 O3 ) nanoparticles were characterized by Fourier transform infrared spectra, X‐ray diffraction, field‐emission scanning electron microscopy. Then, Al2 O3 nanoparticles were employed to improve cure, mechanical, and thermal properties of maleated natural rubber (MNR) nanocomposites. The MNR nanocomposite with 2 phr nano Al2 O3 exhibited excellent value of cure rate index and exceptionally high value of mechanical properties like modulus and tensile strength in comparison to unfilled MNR compound. Thermogravimetric analysis indicated that nano Al2 O3 was able to improve the thermal stability of MNR composites to some extent. Additionally, the present study revealed that the interfacial interaction between MNR and nano Al2 O3 was far better than that between NR and nano Al2 O3 as confirmed from crosslinking degree measurement and morphological analysis. The present article offers a fresh approach to prepare high performance nano Al2 O3 ‐based MNR compounds for future industrial application. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46248. Abstract :